Environmental sensitivity of printed circuit board manufacturing to Cu recycling rate, transportation and various energy sources. (3rd April 2020) - Ozkan, Elif; Bas, Bilge; Elginoz, Nilay; Babuna, Fatos Germirli
This study concentrates on environmental impacts of PCB manufacturing. The objective is to examine the effect of Cu recycling rate, transportation, energy sources and end-of-life (EoL) on global warming potential (GWP), marine aquatic ecotoxicity potential (MAEP), terrestric ecotoxicity potential (TETP), freshwater aquatic ecotoxicity potential (FAETP), human toxicity potential (HTP), ozone layer depletion (ODP), photochemical ozone creation potential (POCP), eutrophication potential (EP), acidification potential (AP) and abiotic depletion potential (ADP fossil, ADP elements) potentials. Increasing Cu recycling rate from 30% to 47%, reduce the impacts by 10 to 103%. The most significant reduction is for HTP. Transportation elevates AP and POCP by 29%, ADP fossil by 23% and GWP by 21%. Obtaining energy from renewable sources causes 56, 40 and 39% reductions in HTP, ADP fossil and GWP, namely. Apart from GWP where PCB manufacturing and EoL has equal impacts, for the other categories PCB manufacturing has more than 75% contribution.